1 - Community Sites of Knowledge: Knowledge Creation and Application for Sustainable Peace in Africa - Andreas Velthuizen, (African Sociological Review, 2013)
In this article the question is asked: What is relationship between knowledge creation and sustainable peace in Africa? The specific aim of this article is to identify specific principles of knowledge creation and sustainable peace that can serve as propositions for further research. The knowledge foundation of this discussion is a literature study, interpretative interaction and participation in focus-groups during field research in collaboration with the Community Sites of Knowledge (CSoK) and the Marcus Garvey Pan African Institute near and in Mbale, Eastern Uganda. It is that knowledge systems are converging towards a glocality of awareness and action. This convergence facilitates the complementarity of endogenous and modern institutions and the inclusive participation of the community as a building block for sustainable peace, transformation and progress. The finding is that relationship of knowledge creation and sustainable peace in Africa is characterized by glocal interconnectedness, the converging of knowledge and central value adding. Some important recommendations are offered to communities, conflict and dispute resolution practitioners, African Universities and state structures concerning the application of endogenous knowledge for sustainable peace.